Evaluation of the spine is critical in the workup of recurrent instability after total hip arthroplasty. (July 2019) - Vigdorchik, J.; Eftekhary, N.; Elbuluk, A.; Abdel, M. P.; Buckland, A. J.; Schwarzkopf, R. S.; Jerabek, S. A.; Mayman, D. J.
Abstract : Aims: While previously underappreciated, factors related to the spine contribute substantially to the risk of dislocation following total hip arthroplasty (THA). These factors must be taken into consideration during preoperative planning for revision THA due to recurrent instability. We developed a protocol to assess the functional position of the spine, the significance of these findings, and how to address different pathologies at the time of revision THA. Patients and Methods: Prospectively collected data on 111 patients undergoing revision THA for recurrent instability from January 2014 to January 2017 at two institutions were included (protocol group) and matched 1:1 to 111 revisions specifically performed for instability not using this protocol (control group). Mean follow-up was 2.8 years. Protocol patients underwent standardized preoperative imaging including supine and standing anteroposterior (AP) pelvis and lateral radiographs. Each case was scored according to the Hip-Spine Classification in Revision THA. Results: Survival free of dislocation at two years was 97% in the protocol group (three dislocations, all within three months of surgery) versus 84% in the control group (18 patients). Furthermore, 77% of the inappropriately positioned acetabular components would have been unrecognized by supine AP pelvis imaging alone. Conclusion: Using the Hip-Spine Classification System in revision THA, we demonstrated a significant decrease in the risk of recurrent instability compared with a control group. Without the use of this algorithm, 77% of inappropriately positioned acetabular components would have been unrecognized and incorrect treatment may have been instituted. Cite this article: Bone Joint J 2019;101-B:817–823.